Association of diabetic retinopathy with systemic organ diseases: a review (cardiovascular and cerebrovascular diseases). (2017) - Sumathy, B.; Poornachandra, S.
The association of Diabetic Retinopathy (DR) with various systemic organ diseases were reviewed in this paper. This imparted much importance, since many of the systemic organs diseases and problems could be predicted well in advance and treated accordingly. With the low cost fundus photograph itself, the future organ failure and diseases could be avoided. In this review paper, the association of DR with the systemic organs namely heart as cardio vascular diseases were discussed. Also, the other diseases like hypertension, cerebrovascular diseases and their relation with DR were reviewed. This paper discussed about the world popular cohort study and its impact with different people from different parts of the world in the vast literature. In the cardiovascular area, Japanese complications study, association of DR and abnormal cardiac structure and function, association of DR with coronary atherosclerosis were discussed with the study methods and their statistical analysis. In the hypertension area, relation of retinal arteriolar narrowing with BP, hypertensions were discussed for different cohort study. The discussion was carried along with the study methods and statistical analysis. In cerebrovascular diseases and stroke, retinal vessel diameters, cerebral diseases and their associations were reviewed under Rotterdam study. Also, retinal microvascular abnormalities and subclinical cerebral infarction were discussed along with study population methods and statistical analysis.